2015
DOI: 10.1016/j.jvs.2014.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, outcomes, and effect on quality of life of cranial nerve injury in the Carotid Revascularization Endarterectomy versus Stenting Trial

Abstract: Objectives Cranial nerve injury (CNI) is the most common neurologic complication of carotid endarterectomy (CEA) and can cause significant chronic disability. Data from prior randomized trials are limited and provide no Health-Related Quality of Life (HRQOL) outcomes specific to CNI. Incidence of CNI and their outcomes for patients in CREST were examined to identify factors predictive of CNI and their impact on HRQOL. Methods Incidence of CNI, baseline and procedural characteristics, outcomes and HRQOL score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 30 publications
1
19
0
5
Order By: Relevance
“…CREST hypothesised that increasing experience would reduce peri-operative complications after CAS. 87 After adjusting for symptom status and patient characteristics, . Thirty day outcomes after carotid artery stenting (CAS) vs. carotid endarterectomy (CEA) in 3467 asymptomatic patients randomised within seven randomised controlled trials (RCTs).…”
Section: Peri-operative Morbidity and Mortalitymentioning
confidence: 99%
“…CREST hypothesised that increasing experience would reduce peri-operative complications after CAS. 87 After adjusting for symptom status and patient characteristics, . Thirty day outcomes after carotid artery stenting (CAS) vs. carotid endarterectomy (CEA) in 3467 asymptomatic patients randomised within seven randomised controlled trials (RCTs).…”
Section: Peri-operative Morbidity and Mortalitymentioning
confidence: 99%
“…However, it has been shown that the majority of CNI will resolve over the first few months and permanent CNI is rare. 21,22 Additionally, this study shows a hospital comparison of outcomes after CEA in symptomatic patients. With the national minimum threshold of 20 CEA per hospital per year, the majority of hospitals have outcomes comparable with the national mean and there are no hospitals performing worse.…”
Section: Discussionmentioning
confidence: 96%
“…[11,12] при наличии высокой ПИ ВСА также выполняли пересечение заднего брюшка двубрюшной мышцы, шилоглоточной, шилоподъязычной мышц с частичной резекцией шиловидного отростка. Ряд авторов [13][14][15] обращают внимание на травматичность такого доступа, так как у основания шиловидного отростка проходят ствол лицевого, языкоглоточного нервов, симпатический ствол, добавочный, блуждающий, подъязычный нерв, которые могут быть повреждены при хирургических манипуляциях.…”
Section: Discussionunclassified